2018
DOI: 10.1080/13501763.2018.1528295
|View full text |Cite
|
Sign up to set email alerts
|

Transparency of EU informal trilogues through public feedback in the European Parliament: promise unfulfilled

Abstract: Significant parts of the EU's legislative process remain shrouded in secrecy. In informal trilogues, representatives of the three main institutions negotiate compromises behind closed doors which are subsequently rubber-stamped in public meetings. While most research on (EU) transparency focuses on the availability of documents, this article investigates how much information on trilogue proceedings is shared with the general public through European Parliament (EP) committee meetings as the only forum to which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 40 publications
1
27
0
1
Order By: Relevance
“…Yet, other recent studies have found that the rules officially put in place by the EP might not have the expected formalizing and levelling effect for all trilogue negotiations. Rules on reporting, for example, are not implemented equally across all trilogue negotiations, in fact in a majority of cases rather poorly (Brandsma 2019). Moreover, the conduct of trilogue negotiations is still far from uniform across different policy fields and many negotiation processes depend on committee traditions as much as they depend on formal rules (Roederer-Rynning and Greenwood 2017).…”
Section: The Influence Of Relais Actorsmentioning
confidence: 99%
“…Yet, other recent studies have found that the rules officially put in place by the EP might not have the expected formalizing and levelling effect for all trilogue negotiations. Rules on reporting, for example, are not implemented equally across all trilogue negotiations, in fact in a majority of cases rather poorly (Brandsma 2019). Moreover, the conduct of trilogue negotiations is still far from uniform across different policy fields and many negotiation processes depend on committee traditions as much as they depend on formal rules (Roederer-Rynning and Greenwood 2017).…”
Section: The Influence Of Relais Actorsmentioning
confidence: 99%
“…However, the EP formally requires its chief negotiator in trilogue meetings to report back to the responsible EP committee after each and every trilogue, and these committees do meet in public (European Parliament, 2017: rule 69f). This means that some transparency is created about the decision-making process, though, in practice, the availability and quality of such feedback reports vary greatly, from total absence, to considerable and to extensive information provision (Brandsma, 2019). The degree of transparency that is provided is thus actor-dependent.…”
Section: Transparency Of Legislative Decision-making In the Eumentioning
confidence: 99%
“…An instrument was developed to measure the transparency of the decision-making process through reporting in the EP (Brandsma, 2019). We created a scale that includes the constitutive elements of decision-making transparency: explanation of actors' behaviour during trilogues; justification thereof; and (lack of) bias or framing.…”
Section: Operationalizing Transparencymentioning
confidence: 99%
“…Yet, there is no reason why the flows of information between EU lawmakers and organized interests should stop during the highly pivotal trilogue phase. Trilogues typically last for a six-month period and involve an average of three 'political' level inter-institutional meetings (Brandsma, 2015(Brandsma, , 2018, during which time a range of lobbyists seek information about the progress of discussions, and, where possible, to influence the detail of proposals which challenge their position. A notable exception is the case study by Andlovic and Lehmann (2014).…”
Section: The Case For Studying Trilogue Politicizationmentioning
confidence: 99%
“…One first problem is linked to implementation of these rules. In practice, it turns out for example that the report back in Commission is often perfunctory or non-existent (Brandsma, 2018). Another problem is that the final stage where the Committee presents its position to plenary is often a fait accompli, with plenary reluctant to intervene in what is presented as carefully crafted and fragile agreements made between the knowledgeable negotiating team and the other EU institutions, which in turn are presented as having limited room for manoeuvre.…”
Section: The Ep and Trilogue Reform: Internal Dissension And Reform Pushmentioning
confidence: 99%